2018
DOI: 10.12968/jowc.2018.27.10.692
|View full text |Cite
|
Sign up to set email alerts
|

The significance of collagen dressings in wound management: a review

Abstract: Clinical experience and research has improved our understanding of wound healing which, in turn, has enabled health professionals to aid wound healing and manufacturers to develop modern wound dressings. The significant role of collagen in wound healing has led to the development of numerous products on the basis of this biological material. The main focus of this review is to provide a critical appraisal of publications about collagen and acellular collagen dressings with a fleece-like or spongy structure. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 83 publications
0
45
0
Order By: Relevance
“…A recent mapping study of collagen structure and function suggested that in normal, injured tissue the collagen fibril is in a closed conformation that upon exposure to blood following injury exposes cell- and ligand-binding sites that could promote the wound healing process [ 20 ]. Several recent reviews detail roles of collagen in the skin and wounds [ 1 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Roles For Collagen In the Skin And Woundmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent mapping study of collagen structure and function suggested that in normal, injured tissue the collagen fibril is in a closed conformation that upon exposure to blood following injury exposes cell- and ligand-binding sites that could promote the wound healing process [ 20 ]. Several recent reviews detail roles of collagen in the skin and wounds [ 1 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Roles For Collagen In the Skin And Woundmentioning
confidence: 99%
“…A plethora of formulations of collagen as amorphous gels, sheet or powder forms, combined with other agents (e.g., silver, for the antimicrobial properties, or ethylenediaminetetraacetic acid (EDTA), carboxymethyl cellulose (CMC) or alginate, i.e., collagen enhancers) are available as wound dressings in the market ( Figure 2 ) [ 6 , 7 , 8 , 10 , 46 , 53 , 77 , 96 ]. The sponge/fleece version of collagen has been tested as a cell-free matrix that promoted new tissue formation in a limited study [ 47 , 75 ]. Particulate or powdered collagen have minimal covalent cross-linking and are active upon administration as signaling molecules [ 77 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…With the in-depth study of wound healing process in recent years, various strategies have been developed to attain skin lesion closure, including antibacterial ointments containing enzymatic substances, synthetic growth factors, polyurethane, hyaluronic acid hydrogels, and alginate fiber dressings [3]. However, the ideal curative features such as efficacy in absorbing wound exudates, flexibility, durability and adherence, and low cost are not fully attained yet [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, considering the economic aspects, suitable dressings should not be too expensive in order to avoid the high cost of treatment [ 17 , 18 , 19 ]. Taking into account all the aforementioned criteria, hydrogels, especially those made from natural polymers, have attracted notable attention in the field of tissue engineering [ 3 , 11 , 20 , 21 , 22 , 23 , 24 , 25 ]. They are fabricated using various techniques, such as phase separation, solvent evaporation, porogen leaching, electrospinning, freeze-drying, or supercritical CO 2 drying, which allows for obtaining of porous biomaterials with a high ability to absorb wound exudate [ 6 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%